Chondronectin in human synovial fluid. - Carsons, S (1988)
Chondronectin is a cartilage matrix protein that specifically mediates the attachment of chondrocytes to type II collagen. A monoclonal antibody to chondronectin was used in a competitive enzyme linked immunosorbent assay (ELISA) and Western blot assay to detect, measure, and characterise chondronectin in human synovial fluid. Chondronectin was detected in all 18 rheumatoid and 11 osteoarthritic synovial fluids examined. Chondronectin concentrations in synovial fluid were lower than those in plasma and correlated most strongly with concentrations of synovial fluid albumin and fibrinogen. These results suggest that synovial fluid chondronectin is in part derived from plasma. The role of chondronectin as a marker of cartilage destruction and potential mediator of pannus formation is discussed.